Chapter Metodi innovativi per l'insegnamento della Geomatica: il video a 360° come strumenti per le esercitazioni sui sistemi a scansione 3D - Parisi, Erica (Studi e saggi, 2022)
The chapter illustrates the results of the educational use of 360° video in the field of Geomatics. Geomatics is the discipline that deals with the collection, analysis, and interpretation of spatial data with the contribution of information technologies. The GeCo Lab has been experimenting in the last few years innovative educational approaches supported by multimedia and interactive tools. The goal within the SEPA360 project has been to use the potentialities of 360° videos to simulate surveying activities, by using topography and laser scanning systems, for the documentation of built heritage, to provide teaching supporting materials for different Geomatic courses active at the University of Florence. The final outputs consist of two videos: one non-interactive with an "educational" approach, to introduce some theoretical concepts, and the other one with an "self-evaluation" purpose, with interactions, added in Vivista.